Recognizing the Role of Industry 4.0 Technology in Enhancing Environmental Sustainability - Patel, Kunjal (Digital Repository of Theses - SSBM Geneva, 2025)
The Indian pharmaceutical industry is at the forefront of addressing global challenges related to environmental sustainability and technological transformation. Industry 4.0 technologies, including Cloud Computing, IoT, advanced automation and Artificial Intelligence offer immense potential to increase operational efficiency, reduce environmental impacts, and foster innovation. However, their adoption within the pharmaceutical sector remains uneven, hindered by financial, technical, and organizational barriers. This research provides a comprehensive evaluation of Industry 4.0 technology adoption, analyzing its impacts, challenges, and strategic measures to overcome barriers. Through a quantitative research design, this study collected primary data from 300 professionals across major Indian pharmaceutical companies. The findings reveal high adoption rates for foundational technologies like IoT and Cloud Computing, driven by their operational benefits. Emerging technologies, such as AR and VR, exhibit lower adoption due to significant barriers, including high capital investments, IT security concerns, and insufficient skilled workforce. Despite these challenges, the study highlights substantial environmental and economic benefits, including improved energy efficiency, reduced emissions, and enhanced resource management. The research underscores the influence of government policies, such as Digital India and Make in India, in promoting technological advancements, although their impact varies across regions and sectors. Orion Corporation and Pfizer CentreOne are just two of many worldwide case studies that have shown how these technologies may improve operational efficiency and environmental sustainability Furthermore, the pivotal roles of corporate governance and stakeholder engagement in driving successful adoption were emphasized, with leadership and collaborative strategies emerging as critical enablers. This study contributes to the academic understanding of Industry 4.0 by validating theoretical insights with empirical data and provides actionable recommendations for policymakers and industry practitioners. These include targeted training programs, phased implementation strategies, and stronger policy frameworks to support technology integration. The findings have far-reaching implications for achieving sustainability goals and fostering innovation in the pharmaceutical sector. By addressing the identified barriers and leveraging the opportunities presented by Industry 4.0, the Indian pharmaceutical industry can position itself as a global leader in sustainable and technologically advanced practices.